2020
DOI: 10.21037/tlcr-20-1049
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of a novel CCNY-ALK and ATIC-ALK double-fusion in one patient with ALK-positive NSCLC and response to crizotinib: a case report

Abstract: Anaplastic lymphoma kinase (ALK) rearrangement, one of the common oncogene rearrangements in the mutational history of lung adenocarcinoma, occurs in approximately 5% of non-small cell lung cancer (NSCLC) patients who could be effectively treated with ALK tyrosine kinase inhibitors (TKIs). The earlier phase III PROFILE 1014 study has shown that crizotinib, a first-generation ALK-TKI, significantly improved progression-free survival (PFS) compared with platinum-based chemotherapy in patients with previously unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, only a few of cases have been documented in the literature, which reveal that patients with NSCLC who harbor double ALK fusion (such as NLRC4-ALK and EML4-ALK, CDK15-ALK and EML4-ALK, CCNY-ALK and ATIC-ALK, PRKCB-ALK and EML4-ALK, BCL11A-ALK and EML4-ALK) could benefit from ALK-TKI crizotinib. [9][10][11][12][13] In the present work, the patient is the first reported case that harbors concurrent TAC1-ALK (Tintergenic: A20) and EML4-ALK fusion. We also found that this patient achieved durable response to crizotinib plus radiotherapy with a PFS of 14 months.…”
Section: Discussionmentioning
confidence: 73%
“…To the best of our knowledge, only a few of cases have been documented in the literature, which reveal that patients with NSCLC who harbor double ALK fusion (such as NLRC4-ALK and EML4-ALK, CDK15-ALK and EML4-ALK, CCNY-ALK and ATIC-ALK, PRKCB-ALK and EML4-ALK, BCL11A-ALK and EML4-ALK) could benefit from ALK-TKI crizotinib. [9][10][11][12][13] In the present work, the patient is the first reported case that harbors concurrent TAC1-ALK (Tintergenic: A20) and EML4-ALK fusion. We also found that this patient achieved durable response to crizotinib plus radiotherapy with a PFS of 14 months.…”
Section: Discussionmentioning
confidence: 73%
“…Jiangming et al described a patient with the double ALK fusion EML4-ALK and BIRC6-ALK who received alectinib treatment for 3 months and did not exhibit adverse drug reactions [5]. In addition, some reports also confirmed that patients with double ALK fusions may be sensitive to crizotinib [2,[14][15][16][17][18]. However, not all lung adenocarcinomas with ALK fusion may benefit from treatment with ALK-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Few investigations have focused on the concomitance of double ALK rearrangements because of the low incidence ( Table 5 ). According to our literature search results, only eleven cases have been previously reported, including CCNY-ALK and ATIC-ALK [ 104 ], NLRC4-ALK and EML4-ALK [ 105 ], PRKCB-ALK and EML4-ALK [ 106 ], EML4-ALK and BCL11A-ALK [ 107 ], EML6-ALK and FBXO11-ALK [ 108 ], DYSF-ALK and ITGAV-ALK [ 109 ], ALK-SSH2 and EML4-ALK [ 110 ], ARID2-ALK and EML4-ALK [ 110 ], EML4-ALK and CDK15-ALK [ 111 ], PDK1-ALK and STRN-ALK [ 68 ], as well as ALK-GCA and EML4-ALK [ 112 ], etc. Previous reports confirmed that patients with double ALK fusion may respond to ALK-TKIs.…”
Section: Rare Alk Fusions and Therapeutic Advancesmentioning
confidence: 99%